2017
DOI: 10.1080/20018525.2017.1334508
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cohort of adults with asthma: mortality and participation in a long-term follow-up

Abstract: Background and objective: Asthma is a major public health concern. The aim of this study was to characterize a large population-based cohort of adults with asthma, and to study factors associated with all-cause mortality and non-participation in a long-term follow-up. Design: Random and stratified samples from five population-based cohorts were clinically examined during 1986–2001, and all subjects with asthma were included in the study (n = 2055, age 19–72 years, 55% women). Independent associations between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…Among the strengths of this population study are the high participation rates and limited selection bias, and that our asthma cohort seems to well reflect the distribution of asthma in the Swedish population of same age . A weakness when estimating prevalence might be the long recruitment period, but because both remission and incidence is low among adults we believe this bias is limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the strengths of this population study are the high participation rates and limited selection bias, and that our asthma cohort seems to well reflect the distribution of asthma in the Swedish population of same age . A weakness when estimating prevalence might be the long recruitment period, but because both remission and incidence is low among adults we believe this bias is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The asthma cohort included all patients with physician‐diagnosed asthma, or report of ever having had asthma and, furthermore, those without asthma diagnosis prior to the surveys but who had a medical history of asthma together with physiologically verified bronchial variability or asthma medication, comprising all together 2055 adults. The origins of the cohort, the criteria for inclusion and mortality during follow‐up have been described in detail elsewhere and are summarized in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that post-bronchodilator FEV 1 was reduced in patients with poor asthma control (Table 4). A previous Swedish study reported that FEV 1 was associated with mortality [25], and a similar study from the US indicated that low FEV 1 was associated with increased mortality among patients with asthma [26]. However, in the Swedish study, postbronchodilator tests were available only for parts of the cohort, while it is not clear whether the latter study used pre-or post-bronchodilator spirometry.…”
Section: Plos Onementioning
confidence: 95%